Effect of Renal Stone Formation on Some Renal Related Parameters in Koya City - Ali, Layla K. (Science Journal of University of Zakho, 2015)
The thirty stone former patients (12 men with 18 women) involved in the current study, were attended the Shaheed Khalid Hospital in Koya city between April to November 2013. The cases diagnosed in the hospital by clinical examination followed by kidney urinary bladder KUB x-ray and ultrasonography. Further more thirty healthy person (15 men with 15 women) were also involved in this study as control group. The data of a current study revealed the dominant prevalence of the renal stone type both in men and women was for uric acid stone type, and calcium carbonate, calcium phosphate and calcium oxalate represent moderate types, and cysteine stone type represent the lowest type among involved patients. The stone formation was more prevalence in age group 51-60 that represent 27% of the total included formers. The results showed significant (p< 0.05) elevation in serum creatinine, urea and uric acid levels in both sexes stone formers, whereas serum total protein and albumin levels were significantly lower in both men and women stone formers as compared with the levels in normal healthy group. The hematological results showed significantly lower numbers of RBC number and Hb content in both men and women stone formers , whereas, WBC count and platelets count showed higher numbers in both men and women stone formers as compared normal healthy group.